Dose-independent virulence in phoretic mites that parasitize burying beetles. Issue 10 (September 2019) - Nehring, Volker; Teubner, Heide; König, Sandra
Graphical abstract: Highlights: Virulence is often a consequence of resource competition between parasites and hosts. Virulence thus depends on parasite dose and available resources. In phoretic mites parasitizing burying beetles, we can manipulate both. We found evidence for competition between and among hosts and parasites. However, virulence can be independent of parasite dose. Abstract: Virulence, the negative impact of parasites on their hosts, typically increases with parasite dose. Parasites and hosts often compete for host resources and more parasites will consume more resources. Depending on the mechanism of competition, increasing host resources can benefit the host. Additional resources can also be harmful when the parasites are the main beneficiaries. Then, the parasites will thrive and virulence increases. While parasite dose is often easy to manipulate, it is less trivial to experimentally scale host resources. Here, we study a system with external host resources that can be easily manipulated: Nicrophorus burying beetles reproduce on vertebrate carcasses, with larger carcasses yielding more beetle offspring. Phoretic Poecilochirus mites reproduce alongside the beetles and reduce beetle fitness. The negative effect of mites could be due to competition for the carrion between beetle and mite offspring. We manipulated mite dose and carcass size to better understand the competition between the symbionts. We found that mite dose itself was not a strong predictor of virulence. Instead, the number of mite offspring determined beetle fitness. At larger doses, there was strong competition among adult parental mites as well as mite offspring. While increasing the carcass size increased both host and parasite fitness, it did surprisingly little to alleviate the negative effect that mites had on beetles. Instead, relative virulence was stronger on large carcasses, indicating that the parasites appropriate more of the additional resources. Our results demonstrate an ecological influence on the selection of parasites on their hosts and suggest that virulence can be dose-independent in principle.